Phase I study of intraventricular recombinant tissue plasminogen activator for treatment of posthaemorrhagic hydrocephalus. Issue 1 (July 1996) - Whitelaw, A; Saliba, E; Fellman, V; Mowinckel, M C; Acolet, D; Marlow, N
Abstract : AIM: Phase I study to evaluate intraventricular fibrinolytic treatment with recombinant tissue plasminogen activator (tPA) as a method of clearing blood from the cerebrospinal fluid, and thus preventing permanent hydrocephalus. METHODS: Twenty two preterm infants, aged 7 to 26 days, with progressive posthaemorrhagic ventricular dilatation (ventricular width > 4 mm over 97th centile) received one to five intraventricular bolus injections of 1.0 mg or 0.5 mg tPA at intervals of one to seven days. RESULTS: The mean cerebrospinal fluid concentration of tPA 24 hours after 1 mg was 1860 micrograms/ml. The half life of tPA in cerebrospinal fluid was about 24 hours. Twenty one (95%) infants survived, 12 (55%) without shunt surgery. One infant had secondary intraventricular haemorrhage. CONCLUSION: Intraventricular tPA resulted in survival without a shunt for most of the infants, but with some risk. Failure may have been due to plasminogen deficiency, an inhibitor, or late intervention.